Kemampuan Career Adaptability Siswa SMK: Studi Literatur - Gatis Sri Harsantik; Budi Purwoko; Najlatun Naqiyah; Bakhrudin All Habsy (DA'WA: Jurnal Bimbingan Penyuluhan & Konseling Islam, 2025)
Career adaptability is one of the important competencies for Vocational High School (SMK) students in facing the dynamics of the world of work in the Industrial Revolution 4.0 era. This study aims to explore the concept, influencing factors, and effective intervention patterns in developing career adaptability in vocational high school students. This study uses a literature review method with the PRISMA approach to identify and analyze relevant literature. The results of the analysis show that career adaptability is influenced by family support, educational interventions such as career guidance and experiential learning, and an understanding of the dynamics of the world of work. In addition, the dimensions of career adaptability, namely career awareness, career control, career curiosity, and career confidence, can be developed through programs designed collaboratively between schools, families, and the industrial world. This study concludes the importance of a holistic approach in improving the career adaptability of vocational high school students so that they are able to face career challenges adaptively and competitively.